Disorderly Differences: Recognition, Accommodation, and American Law - Berkowitz, Roger (2013)
In January 1992, People magazine ran a story entitled Die, My Daughter, Die! ' describing the murder of sixteen-year-old Tina Isa, the daughter of Zein and Maria Isa, Palestinians who emigrated with their seven children to the United States from the West Bank in 1985. Opposite a half-page photo of Zein in a bloodstained sweater, the People article explained that he had hoped to arrange a marriage for Tina, as he had for her three older sisters. He wanted Tina to return to his native village and marry a relative of one of his sons-in-law. Tina resented and resisted her father's plans concerning her marriage and defied the strict, traditional values of her parents by taking a job and dating an African-American schoolmate. As a result, Tina and her father had frequent fights during which he warned her about her offensive behavior (e.g., allowing herself to be seen in public with her boyfriend) and threatened to vindicate the family's damaged honor. On the night of Tina's death, Zein again confronted her and accused her of shaming the family by virtue of her allegedly promiscuous behavior. Then, while Tina's mother held her down, Zein stabbed Tina to death with a seven-inch knife. Charged with first-degree murder, the Isas presented a cultural defense. They claimed that they should not be found guilty since what they did to Tina would not have been treated as a serious crime in their homeland. They maintained that they were obeying the law as they (and Tina) knew and understood it, and that Tina's disobedience called for her punishment. The Isas' cultural defense failed, as it generally does, and they were each convicted of first-degree murder and sentenced to death